1998
DOI: 10.1007/s004290050157
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E- and P-cadherin during tooth morphogenesis and cytodifferentiation of ameloblasts

Abstract: Cell-cell adhesion is fundamental in morphogenesis and is known to be mediated by several groups of cell adhesion molecules. Cadherins are a group of such molecules involved in the Ca2+-dependent cell-cell adhesion mechanism and are found in most kinds of tissue. In this study using indirect immunofluorescence microscopy, we analyzed the distribution of two kinds of cadherins, E- and P-cadherin, in developing tooth germs. In the molar tooth germs at the early bud stage, marginal cells of the epithelial tooth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…The distributions of integral membrane proteins forming intercellular junctions such as occludin, claudins, cadherins, and connexins in ameloblasts have been reported previously (Inai et al, 1997;Obara et al, 1998;Joã o and Arana-Chavez, 2004;Bello et al, 2007;Ohazama and Sharpe, 2007). Early and late differentiating rat ameloblasts at the bell stage expressed claudin-1 at the proximal and distal TJs and also expressed occludin except for the distal TJs of late differentiating ameloblasts (Joã o and Arana-Chavez, 2004).…”
supporting
confidence: 62%
“…The distributions of integral membrane proteins forming intercellular junctions such as occludin, claudins, cadherins, and connexins in ameloblasts have been reported previously (Inai et al, 1997;Obara et al, 1998;Joã o and Arana-Chavez, 2004;Bello et al, 2007;Ohazama and Sharpe, 2007). Early and late differentiating rat ameloblasts at the bell stage expressed claudin-1 at the proximal and distal TJs and also expressed occludin except for the distal TJs of late differentiating ameloblasts (Joã o and Arana-Chavez, 2004).…”
supporting
confidence: 62%
“…Previous studies revealed that nectin deficiency caused alterations in cellular junctions including adherens, tight and desmosomal junctions (Inagaki et al, 2005;Barron et al, 2008;Takai et al, 2008). During development and enamel formation, SR and SI cells are connected by adherens and desmosomal junctions (Fausser et al, 1998;Obara et al, 1998;Gritli-Linde et al, 2002). Our immunohistological analysis revealed severe reduction in the membrane localization of the adherens junction molecule E-cadherin, as well as of the desmosomal junction component desmoplakin, in the SI of the compound mutants ( Fig.…”
Section: Desmosomal Junctions Between Si Cells and Ameloblasts Are Imsupporting
confidence: 50%
“…2008]. Ameloblasts express E-, N-, and P-cadherins as well as ␤ -catenin and p120-catenin (p120), during dental enamel development [Palacios et al, 1995;Fausser et al, 1998;Obara et al, 1998;Terling et al, 1998;Sorkin et al, 2000;Heymann et al, 2002;Bartlett et al, 2010]. A major pathway for signal transduction by AJs involves the regulation of ␤ -catenin, which can act as either a structural protein at cell-cell junctions or a transcription factor in the cell nucleus [reviewed in Munshi and Stack, 2006].…”
mentioning
confidence: 99%